2010
DOI: 10.3109/07357907.2010.489538
|View full text |Cite
|
Sign up to set email alerts
|

Androgen RegulatesADAMTS15Gene Expression in Prostate Cancer Cells

Abstract: Prostate cancer is a major cause of mortality, largely as a consequence of metastases and transformation to androgen-independent growth. Metalloproteinases are implicated in cancer progression. A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) are expressed in prostate cancer cells, with ADAMTS-1 and ADAMTS-15 being the most abundant. ADAMTS-15 but not ADAMTS-1 expression was downregulated by androgen in LNCaP prostate cancer cells, possibly through androgen response elements associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…Evidence, however, is emerging that ADAMTS proteins can also function as tumor suppressors. ADAMTS1, ADAMTS12, and ADAMTS15 act as tumor suppressors in prostate, colon, and breast cancer (Porter et al 2006;Moncada-Pazos et al 2009;Viloria et al 2009;El Hour et al 2010;Molokwu et al 2010). Our genetic evidence shows CG4096 has an inhibitory effect on Egfr activity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence, however, is emerging that ADAMTS proteins can also function as tumor suppressors. ADAMTS1, ADAMTS12, and ADAMTS15 act as tumor suppressors in prostate, colon, and breast cancer (Porter et al 2006;Moncada-Pazos et al 2009;Viloria et al 2009;El Hour et al 2010;Molokwu et al 2010). Our genetic evidence shows CG4096 has an inhibitory effect on Egfr activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence analysis, ADAMTS15 contains three potential N -linked glycosylation sites [201]. Molokwu et al have recently reported a potential cleavage within the disintegrin domain resulting in the release of a C -terminal fragment approximately 53 kDa in size [202]. …”
Section: Adamts15mentioning
confidence: 99%
“…ADAMTS15 was found to contain one androgen response element (ARE) in its promoter and 12 ARE’s within the gene itself using NUBIscan online nuclear receptor binding site search tool. Stimulation of an androgen responsive cell line LnCAP with dihydrotestosterone resulted in marked reduction in ADAMTS15 expression levels [202]. …”
Section: Adamts15mentioning
confidence: 99%
“…In addition, along with versican, it is also dysregulated in prostate cancer (24,25). To our knowledge, however, a knock-out mouse model for Adamts15 is currently unavailable, and its biology is poorly described.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aberrant expression of ADAMTS15, along with versican (VCAN), is implicated in prostate cancer progression (24,25), whereas the accumulation of versican in breast, prostate, and ovarian tumors can promote metastasis (26 -28).…”
Section: Amentioning
confidence: 99%